Arranjos institucionais de manejo e extrativismo do açaí nas áreas de uso comum na comunidade de São Carlos do Jamari (RO) - Paula, Milena Camargo de (Universidade Federal de São Carlos, 2021)
Among the Amazon resources used by traditional and riverside communities, the collection of açaí has stood out due to the growing national and international demand for this forest product, and for being characterized as a symbol for Amazonian biodiversity. Empirical analyzes have indicated the potential of populations to structure social arrangements that enable the sustainable use of common resources, such as açaí in the Amazon. Incentives for policies for the inclusion of populations in the management of extractive territories and in the management of local resources indicate that they are not degraded, tending to keep community organizations economically sustainable. In this case study, we analyze the community that works in the collection of açaí-da-mata (Euterpe precatoria Mart.) within the Amazon forest, in the region of the baixo Rio Madeira, in the state of Rondônia. It refers to the community of São Carlos do Jamari, district of Porto Velho. The general objective of this research was to describe and analyze how institutional arrangements for the management and extraction of açaí (Euterpe precatoria Mart.) are organized in areas of common use in the community of São Carlos do Jamari (RO). The methodological procedures were qualitatively based, through a literature review, documental research and a script for semi-open interviews. The documents collected were carried out using the technique of content analysis by exploring the material, processing and interpreting the results, in an attempt to understand what are the interferences in the dynamics of collective organization for the use of açai groves in São Carlos do Jamari, as well as, the implications for the conservation of extracted resources. Following the principles of institutional design and variables for the governance of long-term common resources, it is considered that the institutional arrangement found on the açaí resource does not demonstrate collective action that impacts on a better quality of the collected açaí. External natures, mainly those that refer to the influences of market demand and the absence and presence of the State, generating a disruption of the traditional agreements that allowed for the proper management of açaí, but do not represent a total degradation of resources.
Institutional arrangements for the management and extraction of açaí in areas of common use in the community of São Carlos do Jamari (RO)
Keywords: Arranjos institucionais; Recursos comuns; Manejo tradicional; Açaí; Institutional arrangements; Common resources; Traditional management; CIENCIAS BIOLOGICAS; CIENCIAS HUMANAS::SOCIOLOGIA